2019
DOI: 10.1038/s41598-019-50838-1
|View full text |Cite
|
Sign up to set email alerts
|

Anti-aphrodisiac pheromone, a renewable signal in adult butterflies

Abstract: The male butterfly Pieris napi produces the anti-aphrodisiac pheromone methyl salicylate (MeS) and transfers it to the female during mating. After mating she releases MeS, when courted by conspecific males, which decreases her attractiveness and the duration of male harassment, thus increasing her time available for egg-laying. In previous studies we have shown that males produced MeS from the amino acid L-phenylalanine (L-Phe) acquired during larval stage. In this study we show that adult males of P. napi can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Larval feeding experiments with the labelled l -phenylalanine proved that 48 is only produced by males 99 and taken up in the adult stage. 179 Behavioural assays demonstrated that mated females, but also virgins perfumed with 48 , are quickly abandoned by courting males, while females lacking 48 are more attractive. 97 Remating can be observed after 4–6 days.…”
Section: Pieridaementioning
confidence: 99%
See 1 more Smart Citation
“…Larval feeding experiments with the labelled l -phenylalanine proved that 48 is only produced by males 99 and taken up in the adult stage. 179 Behavioural assays demonstrated that mated females, but also virgins perfumed with 48 , are quickly abandoned by courting males, while females lacking 48 are more attractive. 97 Remating can be observed after 4–6 days.…”
Section: Pieridaementioning
confidence: 99%
“…203 While terpene secretions discourage attacks by ants, acid production is rendering the caterpillars less palatable. 204 In several species of the heterogeneous group the h instar secretion was found to contain 2-methylpropanoic acid (178) and 2-methylbutanoic acid (181) as major constituents, together with their methyl (179,182) and ethyl esters (180, 183, Fig. 37).…”
Section: Miscellaneous Speciesmentioning
confidence: 99%
“…Mate guarding can persist even when the male is not physically present. This happens when antiaphrodisiac pheromones are transferred to the female, which makes her unattractive to other males (Mozuraitis et al, 2019). A similar process is the formation of a mating plug, which is the result of the coagulated male's ejaculate that blocks the female's reproductive tract and prevents sperm from rival males to enter the sperm storage organs (Polak et al, 2001).…”
Section: Mechanisms Of Sperm Competitionmentioning
confidence: 99%